Comparison of the structure and immunomodulatory activity of polysaccharides from fresh and dried longan. (January 2021) - Gan, Tingsheng; Feng, Chao; Lan, Haibo; Yang, Ruili; Zhang, Jiachao; Li, Congfa; Li, Wu
Graphical abstract: Highlights: Structures and bioactivity of polysaccharides from fresh and dried longan were studied. Drying remarkably changed the structure and bioactivity of longan polysaccharides. Drying increased the degree of branching in longan polysaccharides. DLP exhibited a stronger effect on lymphocyte proliferation and activating macrophages. Abstract: The structures and immunomodulatory activities of purified neutral polysaccharides from fresh (FLP) and hot air-dried (DLP) longan were comparatively investigated. FLP was composed of mannose and glucose at a molar ratio of 0.59:1 with average molecular weight of 1.31 × 10 7 g/mol, and DLP was composed of rhamnose, mannose, glucose and galactose at a molar ratio of 0.2:0.21:1:0.2 with average molecular weight of 1.06 × 10 7 g/mol. Methylation and NMR data showed that FLP was primarily composed of →6)-α-D-Glc p -(1→, and that DLP was primarily composed of →6)-α-D-Glc p -(1→, →3)-β-D-Glc p -(1→, →3)-β-D-Gal p -(1→ and →3)-α-L-Rha p -(1→. FLP and DLP significantly enhanced lymphocyte proliferation, phagocytosis and NO, IL-1β and IL-6 production by macrophages. The drying process increased degree of branching and significantly affected the immunomodulatory activity of longan polysaccharides. DLP exhibited a strong effect on stimulation of the proliferation of lymphocytes and the activation of macrophages. The knowledge of effects of drying process on the structures and bioactivity of longan polysaccharides can aid in illuminating the basis for application of dried longan in the functional foods and medicines production.